2020
DOI: 10.3390/biom10111535
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Attenuating Biosynthesis, Processing, and Activity of Ras Oncoproteins: State of the Art and Future Perspectives

Abstract: RAS genes encode signaling proteins, which, in mammalian cells, act as molecular switches regulating critical cellular processes as proliferation, growth, differentiation, survival, motility, and metabolism in response to specific stimuli. Deregulation of Ras functions has a high impact on human health: gain-of-function point mutations in RAS genes are found in some developmental disorders and thirty percent of all human cancers, including the deadliest. For this reason, the pathogenic Ras variants represent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 213 publications
(314 reference statements)
0
8
0
Order By: Relevance
“…As previous reports show an interaction of natural compounds and Ras (Appari et al, 2014; Tisi et al, 2020), we investigated the ability of ERU to directly activate Ras. Ras activation was studied by immunoblotting of pulled down Ras‐RAF complets.…”
Section: Resultsmentioning
confidence: 99%
“…As previous reports show an interaction of natural compounds and Ras (Appari et al, 2014; Tisi et al, 2020), we investigated the ability of ERU to directly activate Ras. Ras activation was studied by immunoblotting of pulled down Ras‐RAF complets.…”
Section: Resultsmentioning
confidence: 99%
“…According to several studies, quercetin can prevent Ras proteins from being expressed. In one study, quercetin was found to inhibit the expression of Harvey rat sarcoma (H-Ras), K-Ras, and neuroblastoma rat sarcoma (N-Ras) in human breast cancer cells, leading to decreased proliferation and increased apoptosis [ 109 ]. For instance, using several human cancer cell models, quercetin was shown to preferentially reduce the oncogenic Ras protein over wild-type Ras by a post-translational mechanism.…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…Therefore, as shown in Figure 3 , the enhanced expression of LC3-II in the stromal cells of ovarian cancer may fuel the growth of cancer cells. Natural products have historically been regarded as different doctrines of traditional medicine or folk medicine for the management and treatment of a variety of human diseases, including cancer, by inhibiting autophagy pathways [ 4 , 44 , 45 ]. Several studies have shown that the inhibition of autophagy using natural compounds can effectively enhance the cancer cell death induced by diverse anticancer drugs.…”
Section: Natural Products As Inhibitors Of Autophagy In Cancermentioning
confidence: 99%